Draft Annual Plan 1982-83 Vol II Sectoral Programmes Government of Tripura - Planning Commission (Planning Commission, 1982)
By the end of Sixth Plan, the population of Tripura is expected to go upto 23.50 lakhs as against the population of 15.56 lakhs as per 1971 census. There will, therefore, be increase demand for food grains and other agricultural products to meet the demand of increased population. the State at present has a small deficit of food grains. the State is also deficient in the production of oil seeds, pulses and sugarcane. the Sixth Plan vis-a-vis the Annual Plan has been drawn up to increase the production of cereals, pulses, oil seeds, Sugarcane, jute and Mesta etc. as far as possible mostly through intensive and improved agriculture.
Government of Tripura